Sæcula Sæculorum: Missionary Ecclesiology and the Church-World Relationship - Schlesinger, Eugene R. (Open theology, 2016)
This article examines the relationship between church and world in order to provide a theological basis for a missionary ecclesiology. From Vatican II’s Pastoral Constition on the Church in the Modern World, Gaudium et spes , I establish that the church’s existence is interior to the world, interior to the human project, and engaged in human history. The church world relationship is one of ontological dependence and reciprocal influence. Latin American voices, especially Ignacio Ellacuría, Jon Sobrino, and the CELAM conferences, provide this consideration with a greater attention to the concrete historical conditions in which real women and men live. A recognition that mission arises from the demands of the church’s catholicity, and an engagement with Ellacuría’s and Sobrino’s notion of the crucified peoples as a site of encounter with Christ, reconfigures the missionary relationship. The church is not simply the world’s benefactor, but is itself the beneficiary of the world.